The Impact of User Generated Content (Online Review) Towards The Intention to Purchase on E-commerce In Jakarta. Case Study Of Tokopedia. - Prisca Ivana; Robert La Are (ADI Publisher, 2020)
The existence of the internet has taken over most of the traditional ways to do things. The Internet as well provides convenience towards all industries. For example, the emergence of e-commerce Tokopedia 10 years ago makes purchasing and selling goods easier and evenly. Goods are able to be sent all over the world in just one click. However, due to the online market, goods are not able to be touched and observed. User Generated Contents or can be called as online reviews play an important role in customers purchase decisions. Previous experience shared online helps potential customers to predict and have a view over the product. The model used in this study to measure the variable of UGC is Perceived Credibility and Perceived Usefulness as determinants of the Intention to Purchase on E-Commerce Tokopedia. The results found that Perceived Credibility had a significant influence towards the intention to purchase as well as the Perceived Usefulness. From this finding, it provides the recommendation for both management and future research..